Healthcare Reimbursement Models and Orthopaedic Trauma: Will There Be Change in Patient Management? A Survey of Orthopaedic Surgeons. Issue 2 (February 2015) - Ihejirika, Rivka C.; Sathiyakumar, Vasanth; Thakore, Rachel V.; Jahangir, Amir Alex; Obremskey, William T.; Mir, Hassan R.; Sethi, Manish K.
Abstract : Objectives: Healthcare reimbursement models are changing. Fee-for-service may be replaced by pay-for-performance or capitated care. The purpose of this study was to examine the potential changes in orthopaedic trauma surgery patient management based on potential shifts in policy surrounding readmission and reimbursement. Methods: An e-mail survey consisting of 3 case-based scenarios was delivered to 375 orthopaedic surgeons. Five options for management of each case were provided. Each of the 3 cases was presented in 3 different healthcare settings: scenario A, our current healthcare setting; scenario B, in which 90-day reoperation or readmission would not be reimbursed; and scenario C, in which a capitated healthcare structure paid a fixed amount per patient. Results: The response rate was 40.3% with 151 surgeons completing the survey. A 71.1% of the respondents were in private practice settings, whereas 28.3% were in academic centers. In each case, there was significant increase in the respondents' choice to transfer patients to tertiary care centers under both the capitated and penalization systems as compared with the current fee-for-service model. Conclusions: This survey is the first of its kind to demonstrate through case-based scenarios that a healthcare system with readmission penalties and capitated reimbursement models may lead to a significant increase in transfer of complex orthopaedic trauma patients to tertiary care centers. Physicians should be encouraged to continue evidence-based medicine instead of making decisions due to finances, and other avenues of healthcare savings should be explored to decrease patient transfer rates with healthcare changes. Abstract : Supplemental Digital Content is Available in the Text.